A comparison study of Mg/Ca-, alkenone-, and TEX86-derived temperatures for the brazilian margin - Bahr, André; Jaeschke, A.; Hou, A.; Meier, Karl J. F.; Chiessi, C. M.; Albuquerque, Ana Luiza Spadano; Rethemeyer, J.; Friedrich, Oliver (Paleoceanography and paleoclimatology, 2023)
The reconstruction of accurate sea-surface temperatures (SST) is of utmost importance due to the ocean's central role in the global climate system. Yet, a number of environmental processes might bias reliable SST estimations. Here, we investigate the fidelity of SST reconstructions for the western tropical South Atlantic (WTSA) for the interval covered by Marine Isotope Stages (MIS) 6-5, utilizing a core collected off eastern Brazil at ∼20°S. ...